PEREMPUAN DALAM TRADISI SPIRITUALITAS ISLAM LOKAL - Zahro, Fatimatuz (IAIN Tulungagung, 2018)
Islam offers an achievement of the perfection of the soul through the path of mysticism (Sufism). This tradition is known as Sufism. Unfortunately that mystical experience is not much experienced by women. Women are placed in the second class, not only in matters of formal law (sharia), but also in terms of spirituality. Such lameness situation is the effect of patriarchism. Based on this anxiety, researcher uses an ethnographic method with a feminist perspective. In this study, data collection was carried out by means of participatory observation and open in-depth interviews. The results of the study show that the Local Islamic tradition applies more life that glorifies the egality between men and women. Women are given the same space in expressing their diversity. Kata kunci: Women, Spirituality, Local Islam Islam menawarkan suatu pencapaian kesempurnaan jiwa melalui jalan mistisisme (tasawuf). Tradisi demikian dikenal dengan sufisme. Hanya saja pengalaman mistis tesebut nyatanya tidak banyak dicicipi oleh perempuan. Perempuan ditempatkan di kelas kedua, tidak hanya dalam urusan hukum formal (syariah), tetapi juga dalam hal spiritualitas. Situasi kepincangan demikian merupakan karya patriarkisme. Berpijak pada kegelisahan ini, peneliti menggunakan metode etnografi bersperspektif feminisme. Dalam studi ini, pengumpulan data dilakukan dengan cara observasi-partisipasi dan interview terbuka dan mendalam. Hasil penelitian menunjukkan bahwa tradisi Islam Lokal lebih menerapkan kehidupan yang mengagungkan egalitarian antara laki-laki dan perempuan. Perempuan diberikan ruang sama dalam mengekspresikan keberagamaannya. Kata kunci: Perempuan, Spiritualitas, Islam Lokal